2023
DOI: 10.3892/mmr.2023.12942
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation of circRNA m6A in an APP/PS1 Alzheimer's disease mouse model

Abstract: Alzheimer's disease (AD) is a chronic neurological disease characterized by memory loss and progressive cognitive impairment. The characteristic AD pathologies include extracellular senile plaques formed by β-amyloid protein deposition, neurofibrillary tangles formed by hyper-phosphorylation of τ protein and neuronal loss caused by glial cell proliferation. However, the pathogenesis of AD is still unclear. Dysregulation of RNA methylation is associated with biological processes, including neurodevelopment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Previously we showed that interaction of MAPT with HNRNPA2B1 and m 6 A RNA mediates the progression of tauopathy ( Jiang L. et al, 2021 ). Other studies of AD indicate that m 6 A dysregulation often occurs in the context of altered expression of m 6 A writers and readers ( Han et al, 2020 ; Huang et al, 2020 ; Deng et al, 2021 ; Zhao et al, 2021 ; Zhang et al, 2023 ). Hence, we examined levels of m 6 A writers and readers in the APP NL-G-F /MAPT P301S mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we showed that interaction of MAPT with HNRNPA2B1 and m 6 A RNA mediates the progression of tauopathy ( Jiang L. et al, 2021 ). Other studies of AD indicate that m 6 A dysregulation often occurs in the context of altered expression of m 6 A writers and readers ( Han et al, 2020 ; Huang et al, 2020 ; Deng et al, 2021 ; Zhao et al, 2021 ; Zhang et al, 2023 ). Hence, we examined levels of m 6 A writers and readers in the APP NL-G-F /MAPT P301S mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we showed that interaction of MAPT with HNRNPA2B1 and m 6 A RNA mediates the progression of tauopathy [23]. Other studies of AD indicate that m 6 A dysregulation often occurs in the context of altered expression of m6A writers and readers [44][45][46][47][48].…”
Section: I)mentioning
confidence: 91%
“…This result was consistent with other groups’ studies where notable reductions in both neuronal m6A methylation and METTL3 expression have been observed in human AD brains compared to those without the condition, as demonstrated by immunoblot analysis [ 75 ]. For circRNA, high-throughput sequencing has revealed significant changes in circRNA m6A methylation in APP/PS1 AD mice compared to control groups [ 76 ]. This result was consistent with another group’s study where METTL3-dependent m6A-modified circular RNA, circRIMS2, was significantly upregulated in APP/PS1 AD mice, which mediated synaptic and memory impairments by activating the ubiquitination of the GluN2B subunit of the NMDA receptor [ 77 ].…”
Section: Rna Modifications In Neurodegenerative Diseasesmentioning
confidence: 99%